Issues and challenges affecting village leadership effectiveness for rural community development in Malaysia - Ahmad, Ani; Silong, Abu Daud (2011)
Village leaderships (VL) play an important role on leading and managing rural community development (RCD). The role of effective village leader is determinant for the success and failure of development projects at rural area. Village leader as the agent of change at local level should possess certain competencies to effectively conduct his role. However leader’s effectiveness also depends on condition. Structure of organization, leader’s competency and suitable working environment are also important for leader to be effective. Thus, the purpose of this paper is to analyze issues and challenges pertinent to Village Development and Security Committee (VDSC) leaders that affect their effectiveness in RCD in Malaysia. A total of seven VDSC leadership issues had been identified through discussion in a two-day workshop organized by Ministry of Rural & Regional Development (MoRRD). Success of RCD is highly dependent on VDSC leadership competences. Issues and challenges that are surrounding this committee should be understood and analyze so that the best solutions can be proposed towards empowering more effective village leadership.